European Resuscitation Council Guidelines 2021: Adult advanced life support. (April 2021) - Soar, Jasmeet; Böttiger, Bernd W.; Carli, Pierre; Couper, Keith; Deakin, Charles D.; Djärv, Therese; Lott, Carsten; Olasveengen, Theresa; Paal, Peter; Pellis, Tommaso; Perkins, Gavin D.; Sandroni, Claudio; et al.
Abstract: These European Resuscitation Council Advanced Life Support guidelines, are based on the 2020 International Consensus on Cardiopulmonary Resuscitation Science with Treatment Recommendations. This section provides guidelines on the prevention of and ALS treatments for both in-hospital cardiac arrest and out-of-hospital cardiac arrest.